A study of causes, investigation and management of structural causes of abnormal uterine bleeding in reproductive age group - Rohidas, Vibhusha S.; Chavan, Niranjan N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abnormal uterine bleeding (AUB) is debilitating condition affecting 14-25% of women of reproductive age. It has significant impact on women’s personal, social, physical and quality of life. Present study is planned to study causes, investigation along with management of structural causes of abnormal uterine bleeding in reproductive age group. Methods: Consecutive type of non-probability sampling was used for selection of study subjects. A total of 100 gynaecology OPD women diagnosed with menorrhagia of 15-45 years age group were enrolled in study. Results: Mean age of the study subjects was between 26-35 years (47%). 67% were from low socio-economic class while 33% were from middle class. Maximum number of women (66%) had symptoms for less than 6 months. 47% presented with Menorrhagia. 89% were Multiparous, and 11% were Nulliparous. Most common structural causes of AUB was leiomyoma (41%) followed by polyps (23%), adenomyosis (17%), endometrial hyperplasia (15%) and endometrial carcinoma (4%). Prevalence of anemia was 73% in present study. Maximum leiomyoma were treated medically while higher percentage of polyps and hyperplasia was treated surgically. Most commonly performed surgery was polypectomy (20%) followed by dilatation and curettage (17%) and myomectomy (15%). Total abdominal hysterectomy was done in 8% cases while radical hysterectomy was done in 2% cases. Conclusions: Benign lesions of endometrium account for majority of cases presenting with AUB in reproductive age group. Other premalignant and malignant causes should also be considered. High prevalence of anemia was observed in these cases. A comparative clinicopathological study will help in arriving at the cause and correct diagnosis. Histopathological examination is one of the major tools in evaluation of abnormal uterine bleeding and helps us in proper management and treatment of cases.